Tante Lala's Comedy: Representation of Symbolic Annihilation on Women in Media - Mahmudah, Zulfatun (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2021)
Tante Lala's comedy is a video depicting a mother who had difficulties while accompanying her child to study during the Covid-19 pandemic. The video shows the character of a mother who is impatient, angry, and even fails to educate her child. Unfortunately, the video went viral on social media and was even made viral by an infotainment program on TV and some media. This paper aims to reveal how the symbolic annihilation of women is practiced and reproduced and how the media presents stereotypes of women as a spectacle. This paper will also explore how female viewers perceive Tante Lala's video content. The research uses a cultural studies approach and critical discourse analysis as the method. The result shows that symbolic annihilation in Tante Lala's Video was represented by various texts, visual images, and text flow. Within 10:6 minutes, various texts' connotations of a woman character are found, contributing to women's symbolic annihilation. Visually, the camera focuses on the face depicting a fierce and bitchy character. Second, symbolic annihilation is represented in the form of media affirmation of the video through news and infotainment. In addition to the form of affirmation, the media also explicitly uses language that discriminates against women's characters. Informants assessed that the content of Tante Lala's video and media reports and infotainment broadcasts related to the video gave a wrong depiction of women. They argue that the media is also considered to have contributed to stereotyping women based on emotion rather than rationality.